Substitusi Labu Kuning (Cucurbita Moschata) Dan Tepung Beras Terhadap Peningkatan Nilai Gizi, ?-Karoten Dan Sifat Sensoris Kue Ombus-Ombus - Agus Duniaji; Dhamas Nurhasanah; Ni Made Yusa (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2016)
The research was conducted to determine the effect of pumpkin and rice flour ratio to Nutrition Value and ?-carotene content of ombus-ombus cake. This research using randomized block design with 5 treatment of substitution of pumkin and flour rice: 0% pumpkin: 100% rice flour, 20% pumpkin: 80% rice flour, 30% pumpkin: 70% rice flour, 40% pumpkin:60% rice flour, 50% pumpkin: 50% rice flour. Those treatment repeated 3 times. Data obtained analyzed with anova, treatment with significant different tested by Duncan test. The results of the research showed that substitution of pumpkin and rice flour gave different effect on water content, ash content protein content, fat content, carbohydrate content, ?-carotene, colour, taste, aroma, and overall acceptance. substitution 50% of pumpkin and 50% rice flour gave the nutrition value of ombus-ombus cake with water 48.70%, ash 6.16%, protein 4.44%, fat 0.18%, carbohydrates 41.58 %, and  ?-carotene 6.31%, while sensories evaluation such as color 4,3 (yellow), flavor 4,4 (like), aroma 4,2 (typical pumpkin) and overall acceptance 4,8 (really like) by the panelists.